Optimal fee structure for efficient lightning networks - Heng, Alvin Jun Ren (2021)
Off-chain transaction handling like the Lightning Network (LN) is among the most promising solutions to solve the scaling challenges in blockchain technology like Bitcoin. At the same time, the LN faces its own challenges like transaction path lengths, centralization of channels (hubs), channel imbalances (depletion), etc. Here we study the effects of payment channel fees on these various factors. To get realistic insights, we based our study on empirical Bitcoin transaction patterns and existing LN structure, and apply a simple form of fee structure with only one tunable parameter, α, that is most influential on the transaction routing paths. We assume the transactions through the LN take the path of the lowest aggregate fees, and found as a consequence that one cannot have short average path lengths and low overall channel imbalances at the same time. A good compromise is to have fees proportional to the square root of the channel capacity, such that reasonably short path lengths and overall balanced channel capacities can be achieved that makes the operation of the LN more sustainable.